The Influence of Maternal and Infant Characteristics on Infant Mortality: A Literature Review - Pebridila, Luthfi; Putri, Ade Suzana Eka; Kasra, Kamal; Nugraha, Fathan Iman (Jurnal Kesmas Jambi, 2025)
The Infant Mortality Rate (IMR) in Indonesia remains above the reduction target set in the Sustainable Development Goals (SDGs) 2030 agenda. IMR serves as an important indicator of health sector quality, reflecting the success of health development. This study aims to examine the influence of maternal and infant characteristics on infant mortality through a literature review. Literature searches were conducted in four main databases: Google Scholar, Garuda Portal, PubMed, and SINTA, using relevant keywords in both Indonesian and English. Inclusion criteria comprised articles published between 2018 and 2024, written in Indonesian or English, and employing observational study designs. A total of 12 eligible articles were analyzed. Study quality was assessed using the STROBE checklist to ensure completeness and transparency in methodology and results reporting. Narrative analysis was conducted to synthesize the influence of maternal and infant characteristics on infant mortality. Results indicate that maternal factors such as gestational age under 37 weeks, fewer than four ANC visits, pregnancy complications, and high-risk maternal age, as well as infant factors including low birth weight (LBW), male sex, asphyxia, and congenital anomalies, increase the risk of infant mortality. LBW was identified as the dominant factor closely linked to prematurity. Efforts to reduce infant mortality should focus on preventing and managing LBW and optimizing pregnancy and neonatal services, especially in rural areas and high-risk groups.